An appreciative approach to middle leader engagement in school improvement - Raynor, Anne (2017)
Much has been written on the importance of increasing leadership capacity in schools and managing systems for leadership development. However, little focus has been given to creating the necessary conditions to facilitate the emergence of leadership in order to support school improvement. Appreciative Inquiry (AI) is a philosophy and method for promoting transformational change within organisations, shifting from a traditional problem-based orientation to a more strength-based approach to change, which focuses on affirmation, appreciation and positive dialogue.